The Isolation of Enterobacteriaceae in Fishing Cat (Prionailurus viverrinus) Food from Chiang Mai Night Safari - Vorawattanatham, Narathip; Kanungpean, Doungjit; Kanatiyanont, Nathavut; Suwantada, Pongthorn; Wattanachai, Suchat; Sringam, Sarawut; Pinyopummin, Anuchai (Journal of Mahanakorn Veterinary Medicine, 2018)
The isolation of Enterobacteriaceae was isolated from raw meat (pork and chicken meat) and cooked meat (pork and chicken meat) of fishing cat food. The total bacterial colony count is 1.34 X 1011cfu/g isolate form raw meat and 1.02 X 1011cfu/g from cooked meat. The total Enterobacteriaceae colony count were cultured from raw meat and cooked meat that found 2.88 X 1011 cfu/g and 2.42 X 1010 cfu/g respectively. Regarding bacterial isolation and identification from raw meat were found Salmonella Choleraesuis, Escherichia coli, Enterobacter cloacae and Providencia rettgeri which were 5.26% of each species. For Serratia marcescens, Proteus marabilis, Hafnia alvei, Erwinia spp. and Citrobacter braakii were found 10.52% of each species. In cooked meat were found 18.8% Salmonella Choleraesuis, Enterobacter cloacae and Citrobacter braakii of each species and 27.27% Proteus marabilis. These bacteria may lead to health problem of fishing cats.